In praise of Geography as a field of study for the climate emergency. Issue 4 (17th August 2021) - Taylor, Peter J.; O'Keefe, Phil
Abstract: We argue that Geography should be centre stage for understanding today's climate emergency. It warrants this position because as a field of study it uniquely straddles physical/environmental and human/social scholarships. In the wider academic world, bringing together scholars across this "cultural" divide has traditionally been difficult, and continues to be so in current responses to human‐induced climate change. Specifically, physical scholarship and science dominate at the expense of social scholarship and science. But it is now widely recognised we are living in a time of climate emergency and this simply will not do. Geography as a field of study that bridges these two forms of knowledge has the potential to become strategically relevant in this situation. The concept of risk that links environment and people from the Natural Hazards paradigm is identified as a way in which a holistic Geography can take an important lead in worldwide scholarly inputs into anthropogenic climate change understanding and consequent policy development. Abstract : Geography as a field of study can provide a bridging link between physical science and social science contributions to understanding anthropogenic climate change. The paper discusses how and why this might come about.